Molecular feature of lasB gene of Pseudomonas aeruginosa isolated from different clinical sources - R Hussein, Khwam (University of Thi-Qar Journal of Science, 2018)
The study was carried out through a period from June to November 2017 from out-patients and in-patients of Al-Hussein Teaching Hospital in Thi-Qar province South of Iraq. A sum of 132 specimens from the hospital facility condition and different clinical samples of various patients were randomly collected and analyzed for diagnosis of Pseudomonas aeruginosa. These clinical specimens were included wound, burn, ear swabs, urine and sputum specimens. Every single specimen was screened to detect of P. aeruginosa by culturing on suitable media, and 36 isolates of P. aeruginosa were distinguished through biochemical tests and using API 20NE system for confirmation the isolates. All P. aeruginosa isolates were tested against nine antimicrobial discs in vitro. They revealed that having different classes and the results demonstrated that variable resistance to the anti-microbial agents. In attempting to the recognizable proof of P. aeruginosa having the DNA, Polymerase chain reaction (PCR) was utilized in light of particular groundwork for 16S rRNA genetic marker. The results demonstrated that PCR has observed to be quick and sensitive and particular for recognizable proof of P. aeruginosa. Furthermore, 16S rRNA was utilized as confirmation feature, while lasB detected as virulence gene also to utilize as pathogenesis quality of the bacteria.